PENGARUH AMILOSA DAN AMILOPEKTIN TERHADAP SIFAT PASTA PATI JAGUNG - Ulyarti, Ulyarti (Jurnal Sains dan Matematika, 2022)
Corn starch is an abundant renewable resource for producing biodegradable food packaging. There has been a lot of effort to increase the capabilities of corn starch in this area including its plasticity. Native starch becomes thermoplastic after heat treatment with plasticizers.  However, the initial properties of corn starch need to be understood before developing it into biodegradable plastic.  This study was aimed to reveal the effect of amilose and amilopectin on the pasting properties of corn starch.  The study used pure amilose and amilopectin and commercial corn starch.  The comparison was made between commercial corn starch and composite starch made from amilose and amilopectin.  The ratio of amilose to amilopectin in the composite starch was 26 : 74, imitating the ratio of the two components in the corn starch.  The result showed that both starches performed different pasting properties.  These data demonstrate that pasting properties of corn starch do not only depend on  the amount of amilose and amilopectin present in the starch. Key words: corn starch, amilose, amilopectin and pasting properties